Child Filiation and Its Implications on Maintenance and Inheritance Rights: A Comparative Study of Regulations and Judicial Practices in Indonesia, Malaysia, and Turkey - Azwar, Zainal; Armi, Mhd. Ilham; Zulfan, Zulfan; Jelani, Ahmad Bakhtiar bin; Nasri, Ahmad Luthfy (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This article analyses the national laws governing child filiation and their implications on the maintenance and inheritance rights of children in Indonesia, Malaysia, and Turkey. This is prompted by the fact that the determination of child filiation in these three countries not only adopts singular fiqh (Islamic jurisprudence) provisions, as some Middle Eastern Muslim countries do but also takes into account cultural values and human rights. Therefore, this article employs a normative-juridical approach by conducting a comparative analysis of the laws in these three countries. The research reveals that the laws in these three countries differentiate child filiation based on the marital status of the parents: maternity, biological paternity, and nasab (lineage) paternity. These three typologies of child filiation have implications for their maintenance and inheritance rights. The laws in these three countries stipulate that children born from valid marriages have both maintenance and inheritance rights from both parents, while children born from unregistered or non-marital unions only acquire these rights from their mothers. Although the laws in these three countries grant maintenance and inheritance rights to children born out of wedlock from the maternal lineage, some judicial decisions in Indonesia and Turkey grant these rights from both parents. The differences in judicial practices among these three countries are attributed to variations in legal systems and the Islamic legal schools adopted. Among the three studied nations, this article finds that the legal frameworks and judicial practices in Indonesia and Turkey are more accommodating to children’s rights compared to those in Malaysia. [Artikel ini menganalisis hukum negara yang mengatur ketentuan filiasi anak dan implikasinya terhadap hak pemeliharaan dan waris anak di Indonesia, Malaysia, dan Turki. Hal ini dipicu oleh fakta bahwa penetapan filiasi anak di ketiga negara tersebut tidak hanya mengadopsi ketentuan fikih secara tunggal, seperti beberapa negara Muslim di Timur Tengah, tetapi juga memperhitungkan nilai-nilai budaya dan hak asasi manusia. Oleh karena itu, artikel ini menggunakan pendekatan normatif-yuridis dengan melakukan analisis perbandingan terhadap hukum di ketiga negara tersebut. Penelitian ini menunjukkan bahwa hukum di ketiga negara tersebut membedakan filiasi anak berdasarkan status perkawinan orang tua: maternitas, paternitas biologis, dan paternitas nasab. Ketiga tipologi filiasi anak ini memiliki implikasi terhadap hak pemeliharaan dan waris anak. Hukum di ketiga negara menetapkan bahwa anak yang lahir dari perkawinan yang sah memiliki hak pemeliharaan dan waris dari kedua orang tua, sedangkan anak yang lahir dari perkawinan yang tidak tercatat atau tanpa ikatan perkawinan hanya memperoleh hak tersebut dari ibunya. Meskipun hukum di ketiga negara memberikan hak pemeliharaan dan waris anak tanpa ikatan perkawinan dari jalur ibu, beberapa keputusan yudisial di Indonesia dan Turki memberikan hak-hak tersebut dari kedua orang tua. Perbedaan dalam praktik peradilan di ketiga negara ini disebabkan oleh perbedaan sistem hukum dan mazhab fikih yang dianut. Dari ketiga negara yang diteliti, artikel ini menemukan bahwa hukum dan praktik peradilan di Indonesia dan Turki lebih akomodatif terhadap hak anak dibandingkan dengan di Malaysia.]